Highly Efficient and Durable Anion Exchange Membrane Water Electrolyzer Enabled by a Fe–Ni3S2 Anode Catalyst. Issue 1 (27th November 2022) - Ding, Guoheng; Lee, Husileng; Li, Zhiheng; Du, Jian; Wang, Linqin; Chen, Dexin; Sun, Licheng
Abstract : Anion exchange membrane water electrolyzer (AEM‐WE) is a promising approach to producing green hydrogen using renewable energy. However, most of the reported AEM‐WEs still use platinum‐group metal‐based catalysts and the performance is far beyond unsatisfactory. Particularly, developing highly active, durable, and earth‐abundant metal‐based oxygen evolution reaction (OER) catalysts is essential to improve energy efficiency and reduce the costs of AEM‐WE. Herein, Ni2 Fe8 /Ni3 S2 /NF catalyst is fabricated in situ on nickel foam by a simple one‐pot hydrothermal reaction. The as‐prepared anode OER catalyst exhibits current densities of 500 and 1000 mA cm −2 at an overpotential ( η ) of 279 and 302 mV, superior to the performance of noble metal‐based catalysts (IrO2, RuO2 ). Coupled with Ni4 Mo/MoO2 /NF, the resulting single‐cell AEM‐WE displays high performance (1.65 V @ 1 A cm −2 ) and high durability (100 h @ 1 A cm −2 ), outperforming most of the reported AEM‐WEs assembled by non‐noble metal‐based catalysts. Additional characterization of the post‐test anode using different spectroscopic techniques further proved that the Ni2 Fe8 /Ni3 S2 /NF is a highly efficient and robust anode in the AEM‐WE device. Abstract : A low‐cost Ni2 Fe8 –Ni3 S2 /NF oxygen evolution reaction catalyst is developed as an anode material for anion exchange membrane water electrolyzer (AEM‐WE). The as‐prepared material displays high energy efficiency and device durability in AEM‐WE when coupled with Ni4 Mo/MoO2 /NF. The experimental results confirm that AEM‐WE equipped with platinum‐group metal‐free catalysts can achieve similar energy efficiency to proton exchange membrane‐WE.